Price Behaviour of Arecanut in the State of Karnataka (India) Under e-tendering Regime - Vivek, M C; Sahana, S; Patil, K K R (Indian Journal of Extension Education, 2021)
Karnataka is said to be a forerunner among Indian states to reform agricultural markets. E-tendering systemÂ was introduced by the state to ensure better price realisation for the farmers. The present study focusses on analysing the behaviour of arecanut prices during pre and post e-tendering period in Shivamogga and Bheemasamudra APMCs. Secondary data on monthly model prices of arecanut were collected from www.krishimaratavahini.kar.nic.in for a period from January 2007 to December 2019. In the selected APMCs, the arecanut prices exhibited a significant positive exponential trend over the years. Intra year variations were observed in arecanut prices. The monthly growth rate of arecanut prices were found to be higher duringÂ the post e-tendering period in comparison to pre e-tendering period. Findings indicate the impact of e-tendering system on arecanut prices and could be attributed to the increased number of traders participating in theÂ tendering process and the improved transparency of the system.